Stream of memory : - Buck, M. Laurel (Shoreline, 1994)
Laurel Buck remembers a spring stream flowing through the cellar of her grandfather's Quebec farmhouse as an ancestral tongue that has licked her memories and infused her attention with messages of the power, the mystery, and the beauties of the natural world.